Halal Governance in Indonesia: Theory, Current Practices, and Related Issues - Fahmi Ali Hudaefi; Irwandi Jaswir (Bank Indonesia, 2019)
Considering Indonesia’s target to lead halal industry worldwide, the discussion upon the current practices of halal governance in the country is critical to get into a comprehensive insight. Several major drawbacks within the previous studies on this topic is found along the followings. There has never been a study that has specifically discussed the term of halal governance substantively or comprehensively investigated the subject matters in Indonesia. Driven by this gap, we set out to review halal governance practices in Indonesia by employing a qualitative method of documentary. In doing so, the present paper firstly discusses the substantive materials upon lines of defense in halal governance that covers the four themes, which the present paper particularly reviews as the current practices in Indonesia. From the present discussion, this paper offers the novelty on the explanation of lines of defense in halal governance, and that of the current practices in Indonesia along with the related issues presently associated with it. In addition, this paper further delivers the applicable advises for the improvement of the practices. This study is relevant for the stakeholders of halal industry including the domestic government agencies, practitioners and academics.